2009
DOI: 10.1111/j.1399-0039.2009.01312.x
|View full text |Cite|
|
Sign up to set email alerts
|

The HLA‐G 14 bp insertion/deletion polymorphism is a putative susceptible factor for active human cytomegalovirus infection in children

Abstract: Human leukocyte antigen-G (HLA-G) expression is a potential factor for the pathogenesis of virus infection. A 14 bp insertion/deletion polymorphism (rs16375) in the 3'-untranslated region of the HLA-G gene is involved in the stability of HLA-G mRNA and HLA-G protein expression. Therefore, the HLA-G 14 bp polymorphism might be involved in human cytomegalovirus (hCMV) infection. To test a possible association between the HLA-G 14 bp deletion/insertion polymorphism and the active hCMV infection, in this study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
(36 reference statements)
2
40
0
1
Order By: Relevance
“…Infection with T. gondii has been associated with genes encoding interferon gamma, tolllike receptors, and the purinergic receptor P2X 7 [41][42][43] . CMV susceptibility is attributed in part to polymorphisms in several genes including those encoding cytokines, toll-like receptors, and other immune response molecules [34,44,45] . Alterations in the HLA region and polymorphisms in genes encoding cytokines are linked to EBV susceptibility [46,47] .…”
Section: Discussionmentioning
confidence: 99%
“…Infection with T. gondii has been associated with genes encoding interferon gamma, tolllike receptors, and the purinergic receptor P2X 7 [41][42][43] . CMV susceptibility is attributed in part to polymorphisms in several genes including those encoding cytokines, toll-like receptors, and other immune response molecules [34,44,45] . Alterations in the HLA region and polymorphisms in genes encoding cytokines are linked to EBV susceptibility [46,47] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that the polymorphism was associated with HLA-G mRNA stability and isoform alternative splicing pattern and influences protein expression level of HLA-G [14 -16]. The significance of this polymorphism association with many disorders, such as human cytomegalovirus infection, human immunodeficiency virus (HIV) vertical transmission, systemic lupus erythematosus, and idiopathic dilated cardiomyopathy have also been addressed [17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…Upregulation of these molecules on NK cell lines has been associated with overexpression of HLA-G, which may facilitate immune evasion [10]. Homozygous carriage of the 14-base pair (bp) deletion polymorphism in HLA-G has been associated with susceptibility to CMV disease [12].…”
Section: Introductionmentioning
confidence: 99%